TINJAUAN HUKUM ISLAM TERHADAP JANJI (WA’AD) DI PERBANKAN SYARI’AH - Muhamad Nadratuzzaman Hosen; Deden Misbahudin Muayyad (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2014)
Review of Islamic Law in terms of promising (waad) at Shariah Bank. This article explains the review of Islamic law in terms of promising in the view of Fiqh. There are any debates or controversies among Islamic Jurists (Fuqaha) that the status of promising is in implementing operational bank. According to some jurists, firstly, promising is mustahab (bounded religion) but promising is not committed with the Law or Ragulations. Secondly, promising is absolutely bounded religion or compulsory to be implemented, thirdly, promising is compulsory depend on requirement of promising (muallaq) with two categories. First category is compulsory even though the requirements are not fulfill and second is not compulsory due to not fulfill requirements. The second opinion is acceptable for authors with some reasons which are discussing in this article. The method of this article used to descriptive analysis focusing the emerging of waad in implementing the operational shariah bank by studying classical literatures and Contemporer in Islamic Law. The aim of this study is to investigate and to explore the rules of waad in Islamic Contracts at Shariah Bank with looking the cause and effect of waad because there is no waad contract in the article of law and regulation in Law System in Indonesia.Keywords: Wa’d, Islamic Bank, DSN-MUI,murabaḥah